2009
DOI: 10.1002/job.586
|View full text |Cite
|
Sign up to set email alerts
|

Leader self‐structure: a framework for positive leadership

Abstract: SummaryWe expand the conceptualization of positive leadership and hypothesize that leaders' ability to influence followers across varied complex situations will be enhanced through the development of a rich and multifaceted self-construct. Utilizing self-complexity theory and other aspects of research on self-representation, we show how the structure and structural dynamics of leaders' self-constructs are linked to their varied role demands by calling forth cognitions, affects, goals and values, expectancies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
134
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 132 publications
(142 citation statements)
references
References 85 publications
0
134
0
Order By: Relevance
“…These rich schemata can facilitate processing future extreme events more quickly and effortlessly and be relied upon until an event presents stimuli that are considered nonroutine that must be interpreted using a more controlled processing framework (Fiske, 1991). Thus as more responses to potential extreme events are practiced, greater complexity will be formed in relevant schemas for individuals (Hannah, Woolfolk, & Lord, 2009;Mumford, Friedrich, Caughron, & Byrne, 2007;Mumford, Zaccaro, Harding, Jacobs, & Fleishman, 2000) and ultimately group mental models (Hannah, Eggers, & Jennings, 2008), promoting naturalistic decision making (Drillings & Serfaty, 1997). Weick (1988) draws from Shrivastava's (1987) concept of triggering events in extreme contexts, which are discernable events that can be linked back to specific acts of human judgment and that can deteriorate under pressure (Staw, Sandelands, & Dutton, 1981).…”
Section: In Situmentioning
confidence: 99%
“…These rich schemata can facilitate processing future extreme events more quickly and effortlessly and be relied upon until an event presents stimuli that are considered nonroutine that must be interpreted using a more controlled processing framework (Fiske, 1991). Thus as more responses to potential extreme events are practiced, greater complexity will be formed in relevant schemas for individuals (Hannah, Woolfolk, & Lord, 2009;Mumford, Friedrich, Caughron, & Byrne, 2007;Mumford, Zaccaro, Harding, Jacobs, & Fleishman, 2000) and ultimately group mental models (Hannah, Eggers, & Jennings, 2008), promoting naturalistic decision making (Drillings & Serfaty, 1997). Weick (1988) draws from Shrivastava's (1987) concept of triggering events in extreme contexts, which are discernable events that can be linked back to specific acts of human judgment and that can deteriorate under pressure (Staw, Sandelands, & Dutton, 1981).…”
Section: In Situmentioning
confidence: 99%
“…In presenting the positive-based concept of Authentic Leadership Development, Luthans and Avolio (2003) suggest the possibility that leader well-being may have a ''contagion effect'' on the well-being of the leader's subordinates. Building upon the positive approach to leadership, our final article by Hannah, Woolfolk, and Lord (2009), provides an enriched theoretical framework and hypothesizes that a leader's ability to influence subordinates is stimulated through the development of a more wellarticulated self-construct. Their theoretical model makes explicit the need for leadership to explicitly focus on positive human cognitions, goals and values and self-regulatory mechanisms.…”
Section: Special Issue Articles: Can Positive Research Build Strongermentioning
confidence: 99%
“…Tadmor and colleagues (2009) posit that individualists may be driving the performance gains for marginals because they exert more active cognitive effort in controlling their own acculturation process. This corresponds to the importance of self-concept clarity in leadership situations (Hannah et al, 2009). Based on these explanations, the dividing factor among marginals may be the degree of mindfulness they exhibit about the tension involved in their simultaneous insider/outsider status.…”
Section: Mindfulness As Mentioned Earlier Bourhis and Colleagues (1mentioning
confidence: 95%
“…For example, Tadmor, Tetlock and Peng (2009) found that marginals developed higher levels of cognitive complexity than separated or assimilated biculturals, and argued that it was because the marginals experienced stronger dissonance, and as a result, learned to see the world in more complex terms. Cognitive complexity helps leaders construe social behaviour as multidimensional, rather than enacting only a small set of the roles global leaders are expected to play (Hannah et al, 2009). Normally, when individuals categorize themselves as a member of a group, they see themselves as an embodiment of a group prototype or standard, containing the societal meanings and norms that guide their behaviour, and processing information through that group's filter (Turner et al, 1987, Hogg andTerry, 2000).…”
Section: Why Some Marginals Have the Potential To Become Global Leadersmentioning
confidence: 99%